Hubungan Stres Akademik dengan Online Student Engagement pada Mahasiswa Universitas Negeri Jakarta - Anniza Nurrahma; Yasmin Nabilah Khoirunisa; Zuniyanti Khoiriyah (Risenologi, 2021)
The distance learning system is one of the Indonesian government's efforts to prevent the spread of the Covid-19. This learning system is also used in higher education. In practice, students as one of the actors in education are required to stay involved in learning well. Various challenges and barriers in learning activity can cause the emergence of academic stress. Previous studies have shown conflicting results regarding the relationship between academic stress and online student engagement. Therefore, the aim of this study is to examine the relationship between academic stress and online student engagement on students of Jakarta State University who are doing a distance learning (N=50). The study used a quantitative method with a correlational study. The sampling technique used is purposive sampling. Data were collected using Dixson’s Online Student Engagement Scale (OSE) and Gadzella’s Student-life Stress Inventory (SSI). The result of data analysis showed the value of correlation coefficient -0,301, p = 0,034 (p<0,05). It can be concluded that there is a negative relationship between academic stress and online student engagement which means that the higher online student engagement, the lower academic stress on college students.